Mineralogical Investigation and Hydrometallurgical Characteristics of Uranium and Rare Earth Elements, Mineralization of El Hammamat Sediments, G. Gattar, Eastern Desert - Egypt - El Nahas, H.A., Abd-El fattah, N. A., El Monsif, M. Z , (Arab Journal for Sciences and Research Publishing, 2016)
The uranium occurrence of GV is considered as perigranitic uranium deposits while all the others are considered as intragranitic ones. The principal economic minerals were separated and identified. Uranophane was found to represent the main uranium mineral while the REEs occur in the form of very fine disseminated grains of light elements or else in the form of heavy elements associated with the iron oxides and clay fraction of the host rock. For geochemical and hydrometallurgical works, a technological sample of (4000ppm U and 3500ppm REE) at the Northern part of the Eastern Desert, Hammamat GV mineralization of G. Gattar was collected. The collected ore material was then subjected to chemical processing involving sulphuric acid leaching and the dissolved U and REE were separated from the obtained leach liquor. Two alternatives have been studied, namely ion exchange for U following oxalate precipitation for the REEs or else selective successive precipitation.
Keywords: Hammamat; Ion exchange; Uranophane; Leaching; exchange; Precipitation